2002
DOI: 10.1177/147323000203000413
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Eating and Body Weight in Patients with Type 2 Diabetes or Hyperlipidaemia

Abstract: This preliminary investigation, involving 422 patients, tested the hypothesis that rate of eating is associated with obesity in patients with type 2 diabetes or hyperlipidaemia at all ages. The patients' eating habits were determined using a questionnaire, and the patients were classified as quick, normal or slow eaters. The body mass indices of the three groups were compared. The body mass indices of the male patients who ate quickly (25.4 ± 0.2 kg/m 2 ) were significantly higher than those of the patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…One preliminary study showed that BMI increased in association with increasing eating rate in diabetic patients, although it did not take into account any confounding factors [8]. One of our co-authors reported an increase in BMI with faster eating rate as assessed by the same questionnaire as that used in the present study and independently of nutrient intake, physical activity or experience of dieting in young females [9].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…One preliminary study showed that BMI increased in association with increasing eating rate in diabetic patients, although it did not take into account any confounding factors [8]. One of our co-authors reported an increase in BMI with faster eating rate as assessed by the same questionnaire as that used in the present study and independently of nutrient intake, physical activity or experience of dieting in young females [9].…”
Section: Discussionmentioning
confidence: 67%
“…The eating rate of obese people has been investigated, and eating slowly has been considered to be a simple and effective therapy for obesity [7]. Recently, several epidemiological studies conducted among healthy participants have shown positive associations between eating quickly and obesity [8][9][10][11][12] and metabolic syndrome [13]. However, it is not certain whether these findings are also applicable to those with abnormal glucose regulation.…”
Section: Introductionmentioning
confidence: 76%
“…Several studies have reported the potential associations in this regard, such as relationship between body mass index (BMI) and mealtimes [19][20][21]. However, other investigations have identified no connection between mealtimes and obesity [22][23][24][25][26]. Thus, the findings in this area are disputable.…”
Section: Introductionmentioning
confidence: 47%
“…Table 1 shows the mean values and correlations of each parameter related to food intake. The total intake time was 367.1 ± 132.1 s (149-704 s), and the number of mouthfuls was 23.5 ± 5.0 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The mouthful weight was 12.1 ± 2.4 g (7.5-16.2 g), and the intake interval was 15.1 ± 5.1 s (7.8-25.7 s).…”
Section: Statisticsmentioning
confidence: 99%
“…However, as one interesting finding, the metabolic risks faced by participants who ate rapidly but not until feeling full were not lower than those of the participants who ate until feeling full but did not eat rapidly. Reports concerning the metabolic risk of rapid eating are extremely rare (5,6) . People who eat rapidly may overeat before the signals of fullness are recognized by the satiety centre of the brain (7)(8)(9) .…”
Section: Discussionmentioning
confidence: 99%